2011
DOI: 10.2215/cjn.09321010
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Vena Cava Diameter and Left Atrial Diameter Measure Volume but Not Dry Weight

Abstract: SummaryBackground and objectives Hypervolemia is an important and modifiable cause of hypertension. Hypertension improves with probing dry weight, but its effect on echocardiographic measures of volume is unknown.Design, setting, participants, & measurements Shortly after dialysis, echocardiograms were obtained at baseline and longitudinally every 4 weeks on two occasions. Among 100 patients in the additional ultrafiltration group, 198 echocardiograms were performed; among 50 patients in the control group, 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 13 publications
6
52
1
1
Order By: Relevance
“…15 Consistently, our results shown that inpost-dialysis, there are more patients classified hypovolemic by ultrasound measurements of the IVC than by conductivity measurement. This difference is due to the time required for transferring the fluid from the interstitial sector to the intravascular one "refilling''.…”
Section: Discussionsupporting
confidence: 87%
“…15 Consistently, our results shown that inpost-dialysis, there are more patients classified hypovolemic by ultrasound measurements of the IVC than by conductivity measurement. This difference is due to the time required for transferring the fluid from the interstitial sector to the intravascular one "refilling''.…”
Section: Discussionsupporting
confidence: 87%
“…Our data are confirmatory in detecting preload sensitiveness of not only transmitral flow Doppler [7,19] but of main tissue Doppler parameters as well [9,20]. Inferior vena cava diameters as expected were significantly modified by dehydration, accordingly to previous studies [17,20,21]. In our population, IVC diameters were significantly reduced after the first one and a half our of HD compared to baseline, while such a difference was no more present at the end of the treament; once again, this finding may be due to the faster UF rate used in the first HD hour.…”
Section: Dehydration During Hd Led To Reduction Of All Main Clinical supporting
confidence: 90%
“…Current assessment of ECF volume status in this population is surprisingly crude. Promising techniques such as online blood volume monitoring, 176 routine measurement of inferior vena cava diameter, 177 noninvasive lung water measurement, 178 lung ultrasound, 179 and routine bioimpedance assessment 180 remain understudied or can actually cause harm. Blood levels of brain natriuretic peptide correlate with left ventricular filling pressures in the general population and in people with non-dialysis-dependent CKD.…”
Section: Preventing/controlling Ecf Volume Overloadmentioning
confidence: 99%